Predicting high-power performance in professional cyclists - Sanders, D.; Heijboer, M.; Akubat, I.; Meijer, K.; Hesselink, M. K. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To assess if short-duration (5 to ~300 s) high-power performance can accurately be predicted using the anaerobic power reserve (APR) model in professional cyclists.